2022
DOI: 10.32604/phyton.2022.016492
|View full text |Cite
|
Sign up to set email alerts
|

Biochar can Increase Chinese Cabbage (Brassica oleracea L.) Yield, Decrease Nitrogen and Phosphorus Leaching Losses in Intensive Vegetable Soil

Abstract: There are few evidences on the effect of biochar on vegetable yield, nitrogen (N) and phosphorus (P) leaching losses under intensive vegetable production soil. The current field plot scale study evaluated responses of Chinese cabbage (Brassica oleracea L.) yield, N and P leaching losses using five N treatments of common N application rate according to local farmers' practice (N100%), reducing 20% or 40% N fertilizer (N80% and N60%), and reducing 40% N fertilizer but incorporating 10 or 20 t/ha biochar (N60% + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…However, there are three main explanations for the long-term promotion effect of biochar on K. First, biochar could promote the activity and quantity of soil microorganisms, including K-dissolving bacteria [39]. Second, a large amount of K absorbed on the surface of biochar can provide nutrients, to some extent, for the growth of plants [40][41][42]. Thus, we found that biochar could significantly increase the K content of leaves [43].…”
Section: Changes In Chemical Properties Over Timementioning
confidence: 80%
“…However, there are three main explanations for the long-term promotion effect of biochar on K. First, biochar could promote the activity and quantity of soil microorganisms, including K-dissolving bacteria [39]. Second, a large amount of K absorbed on the surface of biochar can provide nutrients, to some extent, for the growth of plants [40][41][42]. Thus, we found that biochar could significantly increase the K content of leaves [43].…”
Section: Changes In Chemical Properties Over Timementioning
confidence: 80%
“…Recent studies have proven the biochar capability of increasing Brassica oleracea L. yields, while at the same time avoiding the N and P leaching losses caused by nitrogen fertilization adopted by farmers. The biochar application resulted in mitigating the ammonium, and phosphorous leaching losses by 20-30% and 29-32%, respectively [31]. Another scientific work evaluated wood biochar on two genotypes of cabbage.…”
Section: Of 13mentioning
confidence: 99%
“…This may be bacause that bamboo charcoal itself has a high P content, which increases the level of available P, but the application of large amounts of bamboo charcoal to the soil also leads to a subsequent increase in alkaline oxides in the soil and an increase in soil pH, resulting in a decrease in available P in the soil [26]. Sun et al [27] reported that the application of biochar to soils did not result in significant changes in available P in the soil in the short term.…”
Section: Correlation Analysismentioning
confidence: 99%